Processo de planejamento de reengenharia guiado por avaliação de usabilidade - Díscola Junior, Sérgio Luisir (2004)
Software can be modified since its creation, deployment and maintenace. Many are the reasons for that: missing requirements, misunderstood requirements, bugs, among others. But, there is one strong reason that should be studied: the missing of usability. Many companies, like Nokia and Oracle detected usability as the major reason for the software modification. Software modification can be done using many techniquies: substitution, maintenance or reengineering. The last consists the revitalization of the software project, its modification and implementation. For that, a criterious planning should be done so as this research goal is to establish a Reengineering Planning Process Guided by Usability Evaluation. This planning should be able to evaluuate the usability of the software and turn reengineering guided by this evaluation so as the produced software turns easy to use, learn and make the user satisfied.